Exploring transdiagnostic stress and trauma-related symptoms across the world: a latent class analysis - Stephanie Haering; Marike J. Kooistra; Christine Bourey; Ulziimaa Chimed-Ochir; Nikola Doubková; Chris M. Hoeboer; Emma C. Lathan; Hope Christie; Anke de Haan (European Journal of Psychotraumatology, 2024)
ABSTRACTBackground: Although trauma exposure is universally prevalent, the ways in which individuals respond to potentially traumatic events vary. Between-country differences have been identified as affecting the development and manifestation of transdiagnostic psychological symptoms, but it remains unclear how stress and trauma-related transdiagnostic symptoms and risk patterns differ based on geographic region.Objective: To explore whether there are distinct classes of stress and trauma-related transdiagnostic symptoms and to determine predictors of class membership in a global sample.Method: Participants (N = 8675) from 115 different countries were recruited online between 2020–2022 and completed the Global Psychotrauma Screen, which assesses stress and trauma exposure, related symptoms, and risk factors. A latent class analysis (LCA) was used to identify classes of stress and trauma-related symptoms per world region (African States, Asia-Pacific States, Eastern European States, Latin American and Caribbean States, Western European and Other States, and North America) and the total sample. Likelihood of class membership was assessed based on demographics, characteristics of the potentially traumatic event, and potential risk factors across the world regions.Results: Similar class compositions were observed across regions. A joint latent class analysis identified three classes that differed by symptom severity (i.e. high, moderate, low). Multinomial logistic regression analyses revealed several factors that conferred greater risk for experiencing higher levels of symptoms, including geographic region, gender, and lack of social support, among others.Conclusions: Stress and trauma-related symptoms seem to be similarly transdiagnostic across the world, supporting the value of a transdiagnostic assessment.